2013
DOI: 10.1111/cge.12148
|View full text |Cite
|
Sign up to set email alerts
|

A family with fragile X syndrome, Duchenne muscular dystrophy and ichthyosis transmitted by an asymptomatic carrier

Abstract: The human X chromosome carries regions prone to genomic instability: deletions in the Xp22.31 region, involving the steroid sulfatase gene (STS) cause X-linked ichthyosis; rearrangements in the Xp21.2 region are associated with Duchenne or Becker muscular dystrophies (DMD or BMD); and the Xq27.3 unstable region, containing the (CGG)n repeat expansion in the FMR1 gene is associated with fragile X syndrome. We report on a family with two affected boys, the elder diagnosed with fragile X syndrome, the younger wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…PUDP encodes a member of the haloamide dehalogenase-like ( HAD ) hydrolase superfamily. Diseases associated with PUDP genes include ichthyosis, intellectual disability, X-linked and tricuspid valve stenosis [ 9 , 19 , 20 ]. Our MLPA results demonstrated six duplications in the exon region of STS , partial duplication in the exon and intron regions of NLGN4X , and the exon regions of PUDP , ANOS1 and GPR143 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PUDP encodes a member of the haloamide dehalogenase-like ( HAD ) hydrolase superfamily. Diseases associated with PUDP genes include ichthyosis, intellectual disability, X-linked and tricuspid valve stenosis [ 9 , 19 , 20 ]. Our MLPA results demonstrated six duplications in the exon region of STS , partial duplication in the exon and intron regions of NLGN4X , and the exon regions of PUDP , ANOS1 and GPR143 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The first such patient was reported by Natori et al [ 16 ], who described a 9-year-old boy with DMD whose clinical phenotype overlapped with FXS. Another paper described the independent segregation of FXS and of DMD in two different brothers with the same mother, who apparently carried fragile X on one of her X chromosomes and DMD on the other X chromosome [ 17 ]. On the other hand, in Patient 1, a double event occurred in the carrier mother—namely, an intragenic deletion in the dystrophin gene and an expansion of the CGG repeat in the FMR1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one case of atypical DMD with FXS is known [ 16 ]. Furthermore, one peculiar family is described by Todorova et al [ 17 ], where an asymptomatic mother, carrier of three X-linked disorders, had two boys both suffering from severe ichthyosis, one also with FXS and the other one with DMD.…”
Section: Introductionmentioning
confidence: 99%
“…Mondal et al suggested that rare variants in AFF2 may be the cause for previously unrecognized autism spectrum disorder (ASD) susceptibility locus and may help to explain some of the male excess of ASD [ 33 ]. The other related phenotypes to AFF2 gene are abnormality of metabolism/homeostasis [ 34 ], aggressive behavior [ 35 ], epicanthic fold, and delayed speech and development of language [ 36 ].…”
Section: Discussionmentioning
confidence: 99%